Efficient molecular sexing in dioecious Silene latifolia and S. dioica and paternity analysis in F(1) hybrids - Hobza, R; Widmer, A (Molecular ecology resources, 2008)
Two polymerase chain reaction-based assays have been developed that work in combination with an efficient DNA extraction protocol to rapidly and reliably determine sex in the dioecious plant species Silene latifolia and S. dioica. In addition, one of the assays allows assessing paternity in the F(1) generation of intra- and interspecific matings involving the two species.